Quantitative assessment of gestational sac shape: the gestational sac shape score - Deter, R.L. (2007)
OBJECTIVE: To develop a quantitative method for characterizing gestational sac shape. METHODS: Twenty first-trimester gestational sacs in normal pregnancies were studied with three-dimensional (3D) ultrasonography. The 3D coordinates of surface-point sets were obtained for each sac using 30-, 15- and six-slice sampling. Cubic spline interpolation was used with the 15- and six-slice surface-point samples to generate coordinates for those 30-slice surface points not measured. Interpolated and measured values, the latter from the 30-slice sample, were compared and the percent error calculated. Cubic spline interpolation was used to determine the coordinates of a standard surface-point sample (3660) for each sac in each slice sample. These coordinate data were used to give each sac a standard configuration by moving its center of gravity to the origin, aligning its inertial axes along the coordinate axes and converting its volume to 1.0 mL. In this form, a volume shape descriptor could be generated for each sac that was then transformed into a vector containing only shape information. The 20 shape vectors of each slice sample were subjected to principal components analysis, and principal component scores (PCSs) calculated. The first four PCSs were used to define a gestational sac shape score (GSSS-30, GSSS-15 or GSSS-6) for each sac in a given slice sample. The characteristics of each set of GSSSs were determined and those for the GSSS-15 and GSSS-6 were compared with the GSSS-30 characteristics. RESULTS: Cubic spline interpolations were very accurate in most cases, with means close to 0%, and approximately 95% of the errors being less than 10%. GSSS-30 accounted for 67.6% of the shape variance, had a mean of zero and an SD of 1.1, was normally distributed and was not related to menstrual age (R = −0.16, P = 0.51). GSSS-15 and GSSS-6 had essentially the same characteristics. No significant differences between individual GSSS-30 values and those for GSSS-15 or GSSS-6 were found, indicating the absence of a slice sample effect. CONCLUSION: Using sophisticated mathematical methods, the gestational sac shape, initially represented by the 3D coordinates of 3660 surface points, was converted to a single number, the GSSS. This score had the appropriate properties for quantitatively characterizing normal, first-trimester gestational sac shapes. As it can be obtained from as few as six slices, it should be useful in many clinical situations. This novel approach has the potential for providing quantitative shape information about a variety of biological shapes and how they change over time.